A new fern species Pteris subiriana (Pteridaceae) from India - Das, Piu; Padhye, P.m.; Mazumdar, Jaideep (Phytotaxa, 2019)
A new fern species, Pteris subiriana (Pteridaceae), is described from India. Pteris subiriana is very similar to P. blumeana in frond morphology and having prominent setae above the costules. But Pteris subiriana can be distinguished by the habit of rhizome, rhizome scales and spore morphology. Pteris subiriana grows naturally in Maharashtra, Kerala and Tamil Nadu in India.